INTERNALISASI NILAI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN MAHFUDZAT UNTUK MENINGKATKAN MOTIVASI PESERTA DIDIK DI SDIT MUTIARA QOLBU SUKATANI - Mohamad Hafidz Alghifary; Ferianto (Tadbir: Jurnal Manajemen Pendidikan Islam, 2023)
SDIT Mutiara Qolbu Sukatani is a formal education that instills character education in its students, considering that currently students tend to ignore character education. The research approach used is a qualitative approach. Methods of data collection using observation, data analysis, documentation and interviews. The results of the research show that the application of mahfudzat at SDIT Mutiara Qolbu Sukatani can instill the character values ​​contained in mahfudzat and is able to have a positive impact on learning activities and social interactions of students both in the classroom environment and in the school environment which in the end can also be implemented in family and community environment. Keywords: Internalization of character education values, mahfudzat learning, SDIT